Alpha globin gene copy number and incident ischemic stroke risk among Black Americans - Ruhl, A. Parker; Jeffries, Neal; Yang, Yu; Brooks, Steven D.; Naik, Rakhi P.; Pecker, Lydia H.; Mott, Bryan T.; Winkler, Cheryl A.; Armstrong, Nicole D.; Zakai, Neil A.; Gutierrez, Orlando M.; Judd, Suzanne E.; et al. (Frontiers in Stroke, 2023)
Introduction People with African ancestry have greater stroke risk and greater heritability of stroke risk than people of other ancestries. Given the importance of nitric oxide (NO) in stroke, and recent evidence that alpha globin restricts nitric oxide release from vascular endothelial cells, we hypothesized that alpha globin gene (HBA) deletion would be associated with reduced risk of incident ischemic stroke. Methods We evaluated 8,947 participants self-reporting African ancestry in the national, prospective Reasons for Geographic And Racial Differences in Stroke (REGARDS) cohort. Incident ischemic stroke was defined as non-hemorrhagic stroke with focal neurological deficit lasting ≥24 h confirmed by the medical record or focal or non-focal neurological deficit with positive imaging confirmed with medical records. Genomic DNA was analyzed using droplet digital PCR to determine HBA copy number. Multivariable Cox proportional hazards regression was used to estimate the hazard ratio (HR) of HBA copy number on time to first ischemic stroke. Results Four-hundred seventy-nine (5.3%) participants had an incident ischemic stroke over a median (IQR) of 11.0 (5.7, 14.0) years' follow-up. HBA copy number ranged from 2 to 6: 368 (4%) -α/-α, 2,480 (28%) -α/αα, 6,014 (67%) αα/αα, 83 (1%) ααα/αα, and 2 (<1%) ααα/ααα. The adjusted HR of ischemic stroke with HBA copy number was 1.04; 95%CI 0.89, 1.21; p = 0.66. Conclusions Although a reduction in HBA copy number is expected to increase endothelial nitric oxide signaling in the human vascular endothelium, HBA copy number was not associated with incident ischemic stroke in this large cohort of Black Americans.